Fast Video Compression Method based on Wavelet Transform and Simple Efficient Search Algorithm - Neima, Hikmat Z. (University of Thi-Qar Journal of Science, 2014)
In this paper, a fast video compression method has been proposed. In proposed method, Firstly, frames were transformed using Discrete Wavelet Transform (DWT) in order to reduce computation time. The disparity between each two adjacent frames was estimated by Simple and Efficient Search (SES) algorithm. The result of the Motion Vector (MV) was encoded into a bit stream by Huffman encoding while the remaining part is compressed like the compression that is used in still image. The proposed method produced good results in terms of Peak Signal-to-Noise Ratio (PSNR), CR, and computation time.